Re-examining the New Product Paradox: How Innovation Ambidexterity Mediates the Market Orientation and New Product Development Performance Relationship - Zhao, Anni; Bi, Xinhua; Han, Lei (Frontiers in Psychology, 2021)
More and more well-documented failure of established companies which could not respond to rapid market changes, such as Kodak and Nokia, demonstrate the importance of transferring marketing information into real firm performance. While marketing strategy literature has long advocated the direct impact of strong firm market orientation (MO) on new product development (NPD) performance, scant research has discussed the mediating mechanism of this MO-NPD performance relationship. Using the traditional source–position–performance (SPP) framework, this study focuses on innovation ambidexterity perspective to investigate the mediating mechanism between MO and NPD performance. Then, this study proposed a conceptual framework and propositions to examine the MO - NPD performance relationship further. Theoretical and practical implications of the findings are also discussed.